Measurement of beauty-strange meson production in Pb–Pb collisions at sNN=5.02TeV via non-prompt Ds+ mesons - S. Acharya; D. Adamová; A. Adler; G. Aglieri Rinella; M. Agnello; N. Agrawal; Z. Ahammed; S. Ahmad; S.U. Ahn; I. Ahuja; A. Akindinov; M. Al-Turany; et al. (Physics Letters B, 2023)
The production yields of non-prompt Ds+ mesons, namely Ds+ mesons from beauty-hadron decays, were measured for the first time as a function of the transverse momentum (pT) at midrapidity (|y|<0.5) in central and semi-central Pb–Pb collisions at a centre-of-mass energy per nucleon pair sNN=5.02TeV with the ALICE experiment at the LHC. The Ds+ mesons and their charge conjugates were reconstructed from the hadronic decay channel Ds+→ϕπ+, with ϕ→K−K+, in the 4<pT<36GeV/c and 2<pT<24GeV/c intervals for the 0–10% and 30–50% centrality classes, respectively. The measured yields of non-prompt Ds+ mesons are compared to those of prompt Ds+ and non-prompt D0 mesons by calculating the ratios of the production yields in Pb–Pb collisions and the nuclear modification factor RAA. The ratio between the RAA of non-prompt Ds+ and prompt Ds+ mesons, and that between the RAA of non-prompt Ds+ and non-prompt D0 mesons in central Pb–Pb collisions are found to be on average higher than unity in the 4<pT<12GeV/c interval with a statistical significance of about 1.6σ and 1.7σ, respectively. The measured RAA ratios are compared with the predictions of theoretical models of heavy-quark transport in a hydrodynamically expanding QGP that incorporate hadronisation via quark recombination.